SUPERVISI AKADEMIK DALAM MELAKSANAKAN KURIKULUM MBKM UNTUK MENINGKATKAN KUALITAS PENDIDIKAN DI SMPN 5 PATI - M. Fashihullisan; Ahmad Hariyadi; Gunawan Setiadi; Saaduddin Annasih; Siti Aniqoh Shofwani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the implementation of academic supervision in the implementation of the Merdeka Curriculum as an effort to improve the quality of education at SMPN 5 Pati Regency. Academic supervision has a strategic role in assisting teachers in planning, implementing, evaluating, and reflecting on student-centered learning. In the context of the Merdeka Curriculum implementation, teachers are required to develop flexible, differentiated, contextual learning that is oriented toward strengthening students’ competencies and character. This study employed a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The subjects of the study included the principal, teachers, and educational staff at SMPN 5 Pati Regency. The findings indicate that academic supervision was carried out through several stages, namely supervision planning, classroom observation, feedback provision, reflection, and follow-up mentoring. Academic supervision conducted in a directed, collaborative, and continuous manner was able to improve teachers’ ability to design teaching materials, implement active learning strategies, use diagnostic and formative assessments, and reflect on the learning process. Therefore, academic supervision serves as an important instrument for improving teacher professionalism and the quality of learning at SMPN 5 Pati Regency. This study recommends strengthening supervision based on mentoring, reflective dialogue, and the development of teacher learning communities as a strategy for sustainable improvement in the quality of education.